Risk Factors for 30-day Hospital Readmission for Diverticular Hemorrhage. Issue 4 (April 2019) - Rubin, Jonah N.; Shoag, Daniel; Gaetano, John N.; Micic, Dejan; Sengupta, Neil
Abstract : Introduction: The 2010 Affordable Care Act introduced the Hospital Readmissions Reduction Program to reduce health care utilization. Diverticular disease and its complications remain a leading cause of hospitalization among gastrointestinal disease. We sought to determine risk factors for 30-day hospital readmissions after hospitalization for diverticular bleeding. Materials and Methods: We utilized the 2013 National Readmission Database sponsored by the Agency for Healthcare Research and Quality focusing on hospitalizations with the primary or secondary discharge diagnosis of diverticular hemorrhage or diverticulitis with hemorrhage. We excluded repeat readmissions, index hospitalizations during December and those resulting in death. Our primary outcome was readmission within 30 days of index hospital discharge. Secondary outcomes of interest included medical and procedural comorbid risk factors. The data were analyzed using logistic regression analysis. Results: In total, 29, 090 index hospitalizations for diverticular hemorrhage were included. There were 3484 (12%) 30-day readmissions with recurrent diverticular hemorrhage diagnosed in 896 (3%). Index admissions with renal failure [odds ratio (OR), 1.31; 95% confidence interval (CI), 1.19-1.43], congestive heart failure (OR, 1.30; 95% CI, 1.17-1.43), chronic pulmonary disease (OR, 1.19; 95% CI, 1.09-1.29), coronary artery disease (OR, 1.12; 95% CI, 1.03-1.21), atrial fibrillation (OR, 1.12; 95% CI, 1.02-1.22) cirrhosis (OR, 1.95; 95% CI, 1.29-2.93, performance of blood transfusion (OR, 1.23; 95% CI, 1.15-1.33), and abdominal surgery (OR, 1.24; 95% CI, 1.03-1.49) had increased risk of 30-day readmission. Conclusions: The 30-day readmission rate for diverticular hemorrhage was 12% with multiple identified comorbidities increasing readmission risk. Abstract : Supplemental Digital Content is available in the text.